Governance as a source of managerial discipline - Julian Franks; Colin Mayer (National Bank of Belgium, 2002)
Anglo-American stock markets are much larger than their continental counterparts. Does investor protection and governance explain these differences? Using UK data, we examine four different forms of intervention which are suppose to promote good governance: takeovers, independent directors, outside shareholders, and providers of new finance. Which of these "four horses will win the race?". Institutional shareholders remain passive in the face of poor performance. Takeovers are effective in replacing management but are not focussed on poorly performing companies. Independent directors entrench poor performers and do not discipline management; they are advisors not monitors. The only effective mechanism for replacing management of poor performers and the providers of outside finance. When a poor performer needs outside finance, only then are outside shareholders willing to impose management changes. Is governance in Continental Europe more effective? The answer is not obviously so. Indeed in one important respect Germany looks worse. When there are major changes of ownership, the gains accruing to shareholders are much lower than in the UK or US. Moreover, those gains accrue to large German shareholders. Smaller shareholders hardly gain at all. One explanation is that restructuring German companies is more difficult and more costly than in the US or UK.
Keywords: 330; Corporate Governance; Führungsorganisation; Übernahme; Fremdkapital; Unternehmenserfolg; Institutioneller Investor; Großbritannien; USA; Deutschland